Status of Energy Efficiency in the Western Balkans : A Stocktaking Report - World Bank (World Bank, 2012)
Across the Western Balkan region, countries exhibit relatively high levels of energy intensity, a high energy savings potential among energy end-users, and heavy dependence on imported hydrocarbons. Energy markets would benefit from enhanced demand-side efforts and integrated energy efficiency measures across all sectors. Since most energy infrastructure was built during the 1960s and 1970s, inadequately maintained since the 1990s, and reaching the end of its useful lifespan, now is a crucial time to consider the way forward in the energy sector. The signing of the Energy Community Treaty in 2003 marked the beginning of systematic energy sector liberalization among Western Balkan countries, allowing them to deal with widespread energy sector problems that included, on the demand side, low energy tariffs, lack of payment discipline and, hence, little incentive for energy users to invest in energy efficiency measures. Building each component of the strong enabling environment required for increased Energy Efficiency (EE) across the Western Balkan countries will need cooperation among decision makers at multiple government levels, and capital investment by stakeholders to support projects that use energy more rationally. Investors are attracted to opportunities where a strong national government role and clear regulatory structures help dismantle barriers, establish clear conditions and standards, provide technical information, and facilitate funding for EE technologies. This study examines the status of the enabling environment for demand-side EE across the .Western Balkans, evaluates developments in each country, and offers recommendations on the way forward.